1997
DOI: 10.1038/sj.onc.1200894
|View full text |Cite
|
Sign up to set email alerts
|

RET alternate splicing influences the interaction of activated RET with the SH2 and PTB domains of Shc, and the SH2 domain of Grb2

Abstract: Activating germline mutations of the RET receptor tyrosine kinase are found in the majority of cases of inherited cancer syndrome MEN 2, and inactivating mutations in some cases of dominantly inherited Hirschsprung disease. Using RET activated by a MEN 2 mutation, we show that both the SH2 and PTB domains of the adaptor protein Shc interact with RET, and we identify the PTB domain interaction site. Interaction with both the SH2 and PTB domains of Shc contributes to the transcriptional activation of a serum res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 29 publications
5
90
0
Order By: Relevance
“…The receptor complex also includes (GPI)-anchored proteins GFRa1, 2, 3 and 4 that are required for RET dimerization and dictate ligand selectivity (Baloh et al, 2000;Scott and Ibanez, 2001). After interaction with its ligands, RET undergoes autophosphorylation and then interacts with multiple effectors such as phospholipase C, Shc, enigma, Grb2, Grb7/ Grb10, Src kinase and Ras-GAP (Santoro et al, 1994;Arighi et al, 1997;Lorenzo et al, 1997). Gainof-function mutations of the RET gene have been associated with multiple endocrine neoplasia type 2 (MEN 2), an autosomal dominant inherited cancer syndrome (Mulligan et al, 1993), whereas loss-offunction mutations of RET have been associated with Hirschsprung disease (aganglionosis, HSCR), a frequent congenital intestinal malformation (1 in 5000 live births) characterized by the absence of neural crest-derived parasympathetic neurons of the hindgut (Edery et al, 1994;Romeo et al, 1994).…”
Section: Dependence Receptors: a Short Historymentioning
confidence: 99%
“…The receptor complex also includes (GPI)-anchored proteins GFRa1, 2, 3 and 4 that are required for RET dimerization and dictate ligand selectivity (Baloh et al, 2000;Scott and Ibanez, 2001). After interaction with its ligands, RET undergoes autophosphorylation and then interacts with multiple effectors such as phospholipase C, Shc, enigma, Grb2, Grb7/ Grb10, Src kinase and Ras-GAP (Santoro et al, 1994;Arighi et al, 1997;Lorenzo et al, 1997). Gainof-function mutations of the RET gene have been associated with multiple endocrine neoplasia type 2 (MEN 2), an autosomal dominant inherited cancer syndrome (Mulligan et al, 1993), whereas loss-offunction mutations of RET have been associated with Hirschsprung disease (aganglionosis, HSCR), a frequent congenital intestinal malformation (1 in 5000 live births) characterized by the absence of neural crest-derived parasympathetic neurons of the hindgut (Edery et al, 1994;Romeo et al, 1994).…”
Section: Dependence Receptors: a Short Historymentioning
confidence: 99%
“…[56][57][58] Ligand binding to the RET complex triggers RET autophosphorylation, followed by interaction with effectors that include phospholipase Cg, Shc, Enigma, Grb2, Grb7/Grb10, Src kinase, and Ras-GAP, and resultant downstream signaling. [59][60][61] Mutations in the RET proto-oncogene may be associated with neoplastic disease or with a neural developmental disease. Multiple endocrine neoplasia type 2 (MEN-2) occurs in association with one set of RET mutations, 62 whereas Hirschsprung syndrome occurs in association with a different set of RET mutations.…”
Section: Rearranged During Transfection (Ret): One Receptor Two Disementioning
confidence: 99%
“…We also reported that binding of the Shc PTB domain to tyrosine 1062 in the Ret long isoform is important for the transforming activity of Ret with the C634R or M918T mutation (Asai et al, 1996;Lorenzo et al, 1997;Arighi et al, 1997;Durick et al, 1998). As shown in Figure 4, when tyrosine 1062 in Ret with each kinase domain mutation was replaced with phenylalanine, the transforming activity of the mutant proteins markedly decreased, suggesting the importance of the binding of the Shc PTB domain to tyrosine 1062 for their transforming activity.…”
mentioning
confidence: 92%